Bioimpedance assay for the assessment of volume changes in burn patients treated with and without hyperbaric oxygen therapy - Pradeoth Mukundan Korambayil; Hemang Arvind Sanghvi; Leya Mariam Shibu; Prashanth Varkey Ambookan (Journal of Clinical and Scientific Research, 2025)
Background: Hyperbaric oxygen (HBO) therapy helps with membrane stabilisation and decreases cell death in burn injuries. A bioimpedance assay (BIA) was done to understand the fluid proportion in burn patients, and the clinical progress of the patients was noted. In this study, the bioimpedance assay was done in burns patients to compare the clinical outcome in those who were treated with or without HBO therapy. Methods: The study was carried out at the burn unit, and plastic surgery department from November 2022 to May 2023. The study included 10 patients admitted with 2nd- to 3rd-degree thermal burns and 5%–50% of total body surface area burned. The patients were divided into two groups based on their age, severity of burn injuries and comparable parameters. The age of the patients ranged from 22 to 76 years. The clinical progress and bioimpedance assay were noted on days 0, 3 and 6. The clinical outcome was correlated with the phase angle and predictive marker trends that were noted using the bioimpedance assay. Results: Serial measurements of phase angle and predictive markers demonstrated a significant correlation with the clinical trajectory (improvement or decline) of burn patients. Impending sepsis and surgical intervention were associated with a commensurate deterioration in phase angle trends and predictive markers. Patients treated with HBO therapy exhibited superior clinical outcomes, as evidenced both through bioimpedance assays and clinical parameters. Conclusions: Phase angle and predictive marker trends in bioimpedance assays are potential tools to measure the clinical outcomes of burn patients subjected to HBO therapy.